Converting habits of antibiotic use for respiratory tract infections in German primary care - study protocol of the cluster-randomized controlled CHANGE-3 trial - Wollny, Anja; Kamradt, Martina; Poß-Doering, Regina; Szecsenyi, Joachim; Uhlmann, Lorenz; Kronsteiner, Dorothea; Wensing, Michel (Trials, 2019)
Background: The overuse of antibiotics is a major cause for the worldwide rise of antibiotic resistance. Although it is well known that acute respiratory tract infections (ARTI) are mainly caused by viruses and are often self limiting, antibiotics are too frequently prescribed in primary care. CHANGE-3 examines whether a complex intervention focusing on improving communication and provision of prescribing feedback reduces antibiotic use in patients suffering from ARTI. Methods/design: The CHANGE-3 trial is a cluster-randomized controlled trial nested within a web-based public campaign conducted in two regions in Germany. A total of 114 medical practices will be included. Practices randomized to the intervention will receive a practice-specific antibiotic-prescription feedback and an educational outreach visit. During the visit the whole practice team will receive an introduction to e-learning modules addressing patient-centered communication on antibiotics. Furthermore, the practices will receive tablet PCs with information on antibiotics and the treatment of ARTI to be presented to patients. Practices randomized to the control will provide care as usual. The primary outcome measure is the antibiotic prescribing rate for patients with a history of ARTI. Data collected before the intervention, during the intervention and after the intervention will be compared. The use of narrow- vs. broad-spectrum antibiotics will be analyzed as a secondary outcome. A process evaluation is also part of the trial. Discussion: This study should contribute to the growing body of research on reducing antibiotic prescription. Trial registration ISRCTN, ISRCTN15061174. Registered retrospectively on 13 July 2018.
Gesehen am 16.08.2019